Respuesta :

LIMASH

Answer: x=8

Step-by-step explanation:Let's solve your equation step-by-step.

4X - (3X + 5) =2X - 13

Step 1: Simplify both sides of the equation.

4x−(3x+5)=2x−13

4x+−1(3x+5)=2x−13(Distribute the Negative Sign)

4x+−1(3x)+(−1)(5)=2x−13

4x+−3x+−5=2x−13

4x+−3x+−5=2x+−13

(4x+−3x)+(−5)=2x−13(Combine Like Terms)

x+−5=2x−13

x−5=2x−13

Step 2: Subtract 2x from both sides.

x−5−2x=2x−13−2x

−x−5=−13

Step 3: Add 5 to both sides.

−x−5+5=−13+5

−x=−8

Step 4: Divide both sides by -1.

−x−1=−8−1

x=8